Comprehensive analysis of lipid nanoparticle formulation and preparation for RNA delivery - Md. Anamul Haque; Archana Shrestha; Constantinos M. Mikelis; George Mattheolabakis (Elsevier, 2024)
Nucleic acid-based therapeutics are a common approach that is increasingly popular for a wide spectrum of diseases. Lipid nanoparticles (LNPs) are promising delivery carriers that provide RNA stability, with strong transfection efficiency, favorable and tailorable pharmacokinetics, limited toxicity, and established translatability. In this review article, we describe the lipid-based delivery systems, focusing on lipid nanoparticles, the need of their use, provide a comprehensive analysis of each component, and highlight the advantages and disadvantages of the existing manufacturing processes. We further summarize the ongoing and completed clinical trials utilizing LNPs, indicating important aspects/questions worth of investigation, and analyze the future perspectives of this significant and promising therapeutic approach.